Critical Analysis of Sustainable Healthcare Practices, Green Technologies, And Climate-Health Intersections - Alabdrabalnabi, Baneen Abdulkareem; Al Bashrawi, Sahar Abdullah; Al-Otaibi, Mabrd Khaled; Al-Horri, Heba Mohammed; Al Salem, Sajdah Abdullah M; Alawami, Zainab Ibrahim Hassan; Al jarad, Fadillah Abdullah; Alali, Ahmad Mohammed; Al Talaq, Ali Ibrahim; AL kawher, Ali Yousef (Journal of Ecohumanism, 2024)
Healthcare practices and the earth’s climate are already recognized as major areas of concern in today’s healthcare systems. As the interest grows in how climate change impacts health, the worst thing is that anything that keeps going wrong is because of expansion in the healthcare industry and its negative environmental contribution. This review critically discusses sustainable health care, the adoption of green solutions in the facility, and the relationship between climate change and health. Analyzing the current literature and relevant case studies, this review aims to understand how healthcare organizations can minimize environmental impacts, enhance energy efficiency, and minimize waste. Also, it examines the effects of these practice of practices on health, cost, and sustainability of the health processes. This paper’s findings suggest promising strategies that may help HSs address and overcome climate change complications.